Quantitative interpretation of smectite content in the shale seals of Northern Carnarvon basin, North-West shelf of Australia - Beloborodov, R.; Pervukhina, Marina; Shulakova, Valeriya; Chagalov, D.; Josh, M.; Hauser, J.; Clennell, M. (2018)
© 2018 SEG. Shales are omnipresent in sedimentary basins and generally need to be drilled through to reach conventional or to develop unconventional reservoir. Shales, especially smectite-rich, often cause significant drilling problems associated with overpressure, borehole instability, etc. Understanding of clay mineralogy before drilling is very important to reduce risks associated with drilling. In this study, we perform a simultaneous AVO inversion of a part of the Duyfken seismic survey, the Northern Carnarvon Basin of the North-West Shelf of Australia. Log data from a training well were used to establish correlations between smectite content and acoustic impedance (AI) and VP/VS ratio. It is worth noting that mechanically and chemically compacted shale exhibit two significantly different trends between smectite and a principal component of seismic attributes. The smectite content obtained from surface seismic is in a good agreement with that estimated in a blind test well from the XRD analysis of cuttings.